Clinical Characteristics and Outcomes of Eosinophilic Colitis in Patients With Cancer. (August 2021) - Khurana, Shruti; Abu-Sbeih, Hamzah; Ma, Weijie; Qiao, Wei; Foo, Wai Chin; Richards, David M.; Thomas, Anusha S.; Khan, Anam; Zhang, Hao Chi; Wang, Yinghong
Abstract : Background: Eosinophilic colitis (EoC) is a rare form of eosinophilic gastrointestinal disease characterized by diffuse eosinophilic infiltration in the deep lamina propria of colonic mucosa. The pathophysiology is unclear, but EoC has been associated with multiple known risk factors. Aim: The aim of this study was to characterize the clinical characteristics and disease course of patients with EoC at a major cancer center. Material and Methods: We retrospectively reviewed colonic samples obtained between January 2000 and December 2018 from our institutional database and included cases with significant colonic eosinophilia. Baseline clinical data and EoC-related clinical course and outcomes were documented. Results: Forty-one patients were included. One fourth had coexisting autoimmune conditions. Seventy-eight percent had a cancer diagnosis. Half the patients received chemotherapy, with a median duration of 180 days between chemotherapy and EoC onset. Symptoms were present in 76% of patients. Diarrhea was more prevalent in patients who received chemotherapy (85% vs. 42%). Median duration of EoC symptoms was 30 days in patients with cancer and 240 days in those without cancer ( P =0.03). Most patients (88%) had normal colonoscopy findings. Fifteen percent of patients required hospitalization. All-cause mortality was 37%, mostly related to underlying malignancy and organ failure. Conclusions: EoC in cancer patients appears to have more diarrhea-predominant symptoms, particularly in patients receiving chemotherapy, but a shorter disease duration compared with patients without cancer. Hospitalization can be required for serious cases. Treatment may be reserved for patients requiring symptom management, as most patients with EoC have good clinical outcomes regardless of treatment. Abstract : Supplemental Digital Content is available in the text.